The Salary Scholarship Program implemented in Mexico: Chiaroscuro of a social policy - Yurén, Teresa; Moctezuma, Evelyn; García, Mayné Elizabeth; Lugo, Elisa (Education Policy Analysis Archives, 2019)
In this work we report the results of the documentary analysis of a scholarship program and of the social policy in which it falls, with a double objective: to uncover epistemological and ethical-social deficiencies in its design and operation, and to derive some recommendations for the formulation of policies and programs in the educational field. Methodologically, our first step was to review 13 evaluations of social development programs carried out between 2015 and 2018. The review led us to do a meta-analysis of the evaluations, based on the weaknesses and strengths pointed out by the evaluators. To systematize and make comparisons, we used the Atlas Ti tool (version 7). What stands out in the analysis of the discourse carried out is that the social development policy was not entirely coherent with the purpose established in the corresponding regulations and sought to meet objectives and goals, beyond what was established in the laws. This made the design more complex, made the diagnoses insufficient, made the operation more difficult and moved the programs away from the central objective: overcoming poverty. Furthermore, it is concluded that political will and innovative ideas are not enough for an effective social policy. Good diagnoses are required, based not only on an analysis of the reality that is problematic, but also on a review of available scientific works and articles, and on the results of previous experiences. On this basis, the design of social policy should formulate clear objectives, have a consistent logical and technical structure, and propose viable and precise strategies for action. The same would have to happen with programs derived from social policy.